Kriminalitet og straffepolitik i Island - Helgi Gunnlaugsson (Nordisk Tidsskrift for Kriminalvidenskab)
This article examines the crime rate in Iceland based on crimes known to the police in the time period 1988-1996. Research on the attitudes of Icelanders toward crime-related matters is examined as well. Moreover, research on the impact of a tougher criminal policy to fight the crime problem is evaluated. It is shown that despite a growing crime concern among the general public in Iceland, the amount of crime known to the police has not changed significantly - except for burglaries, which have increased. As for the impact of a stricter crime policy, it is concluded, among other things, that certainty and promptness of punishment is more effective than focusing on harsher sentencing alone.